An Integrated Phenotypic and Genotypic Approach Reveals a High‐Risk Subtype Association for EBF3 Missense Variants Affecting the Zinc Finger Domain. Issue 1 (16th April 2022) - Deisseroth, Cole A.; Lerma, Vanesa C.; Magyar, Christina L.; Pfliger, Jessica Mae; Nayak, Aarushi; Bliss, Nathan D.; LeMaire, Ashley W.; Narayanan, Vinodh; Balak, Christopher; Zanni, Ginevra; Valente, Enza Maria; Bertini, Enrico; et al.
Abstract : Objective: Collier/Olf/EBF (COE) transcription factors have distinct expression patterns in the developing and mature nervous system. To date, a neurological disease association has been conclusively established for only the Early B‐cell Factor‐3 ( EBF3 ) COE family member through the identification of heterozygous loss‐of‐function variants in individuals with autism spectrum/neurodevelopmental disorders (NDD). Here, we identify a symptom severity risk association with missense variants primarily disrupting the zinc finger domain (ZNF) in EBF3 ‐related NDD. Methods: A phenotypic assessment of 41 individuals was combined with a literature meta‐analysis for a total of 83 individuals diagnosed with EBF3 ‐related NDD. Quantitative diagnostic phenotypic and symptom severity scales were developed to compare EBF3 variant type and location to identify genotype–phenotype correlations. To stratify the effects of EBF3 variants disrupting either the DNA‐binding domain (DBD) or the ZNF, we used in vivo fruit fly UAS‐GAL4 expression and in vitro luciferase assays. Results: We show that patient symptom severity correlates with EBF3 missense variants perturbing the ZNF, which is a key protein domain required for stabilizing the interaction between EBF3 and the target DNA sequence. We found that ZNF‐associated variants failed to restore viability in the fruit fly and impaired transcriptional activation. However, the recurrent variant EBF3 p.Arg209Trp in the DBD is capable of partially rescuing viability in the fly and preserved transcriptional activation. Interpretation: We describe a symptom severity risk association with ZNF perturbations and EBF3 loss‐of‐function in the largest reported cohort to date of EBF3‐related NDD patients. This analysis should have potential predictive clinical value for newly identified patients with EBF3 gene variants. ANN NEUROL 2022;92:138–153